Suboptimal HIV Pre-exposure Prophylaxis Awareness and Willingness to Use Among Women Who Use Drugs in the United States: A Systematic Review and Meta-analysis. - Zhang, Chen; McMahon, James; Simmons, Janie; Brown, L. Lauren; Nash, Robertson; Liu, Yu (AIDS & Behavior, 2019)
In the United States (U.S.), more than 12 million women reported illicit drug use in the past month. Drug use has been linked to increased risk for HIV, but little is known about the uptake of HIV pre-exposure prophylaxis (PrEP) to prevent HIV among women who use drugs (WWUD). Following the PRISMA guideline, we conducted a multi-database literature search to assess engagement along the PrEP care continuum among WWUD in the U.S. Seven studies with a total of 755 women were included in the review: 370 (49%) Black, 126 (16.7%) Hispanics, and 259 (34.3%) Whites. Employing random-effect models, data indicate 20.6% (95% CI 8.7%, 32.4%) of WWUD were aware of PrEP, and 60.2% (95% CI 52.2%, 68.2%) of those aware were also willing to use PrEP. Notwithstanding study limitations, our findings suggest there may be potential to increase PrEP uptake among WWUD, but efforts must first concentrate on improving PrEP awareness among this population.